Racemose neurocysticercosis - Palacios-Ordóñez, Enver Vantroi (2019)
A 44-year-old woman who entered to emergency room presenting holocraneal, progressive and intense headache, explosive vomits and progressive right hemiparesis associated with multiple falls. The images showed a cystic formations conglomerate in the left silvian valley and at top of pretroncal cistern and not enhanced by contrast, considering the diagnosis of racemose neurocysticercosis.